Molecular interactions from the density functional theory for chemical reactivity: Interaction chemical potential, hardness, and reactivity principles - Miranda-Quintana, Ramón Alain; Heidar-Zadeh, Farnaz; Fias, Stijn; Chapman, Allison E. A.; Liu, Shubin; Morell, Christophe; Gómez, Tatiana; Cárdenas, Carlos; Ayers, Paul W. (Frontiers in Chemistry, 2022)
In the first paper of this series, the authors derived an expression for the interaction energy between two reagents in terms of the chemical reactivity indicators that can be derived from density functional perturbation theory. While negative interaction energies can explain reactivity, reactivity is often more simply explained using the “|dμ| big is good” rule or the maximum hardness principle. Expressions for the change in chemical potential (μ) and hardness when two reagents interact are derived. A partial justification for the maximum hardness principle is that the terms that appear in the interaction energy expression often reappear in the expression for the interaction hardness, but with opposite sign.